Production and characterization of uricase from pseudomonas otitidis strain SN1 isolated from a hot spring - Irwan Shah Lee, Nor Sahslin (2019)
Uricase is an enzyme that catalyzes the oxidation of uric acid to allantoin. This study aimed to exploit bacteria isolated from hot springs to produce uricase using uric acid as substrate. Sampling was conducted at Hulu Langat hot springs and the samples were enriched in LB medium followed by inoculation into uric acid minimal medium. The isolated bacteria were screened for uricase production using plate assay method. One-factor-at-a-time (OFAT) methodological optimization was used to enhance uricase production from the selected bacteria. Uricase was then purified using anion exchange and gel filtration chromatography prior to its characterization. Four bacterial strains positive for uricase enzyme activity were successfully isolated and were identified as Pseudomonas otitidis strain SN1, Pseudomonas sp. strain SN2, Pseudomonas stutzeri strain SN3 and Pseudomonas sp. strain SN4. P. otitidis strain SN1 showed the highest uricase activity (0.12 U/mg) and was selected for further study. Optimized uricase production of strain SN1 was achieved with uric acid minimal medium supplemented with 2% (w/v) glucose, 0.2% (w/v) uric acid, 2% (w/v) yeast extract, and adjusted to pH 7.2. Statistical analyses showed that all variables were significant parameters that affect the production of uricase. The uricase was successfully purified to homogeneity using 70% (w/v) ammonium sulfate precipitation, HiTrap™ Q Sepharose HP anion exchange chromatography and Superdex G-75 gel chromatography. The specific activity of uricase was increased by 3.52 fold, from 0.058 U/mg for crude to 0.204 U/mg for purified uricase. The purified uricase showed a size of approximately 35 kDa band on SDS PAGE gel. The kinetics of purified uricase was 16.54 |iM and 0.2 U/mg (Vmax). The purified uricase exhibited an optimum activity at 35°C and pH 8.5. The enzyme was stable from pH 8.0-9.0 and was able to retain 50% of its total activity after incubation for 30 minutes at 50°C. Activity of uricase was retained in the presence of metal ions (Cu2+, Fe2+, Mn2+) and detergent (urea). The band corresponding to the expected size of uricase, was sent for mass spectrometry analysis for protein identification. However, the results showed that the peptide sequences matched that of ornithine carbamoyltransferase (score=780). The discrepancy was probably due to the presence of low abundance of uricase which resulted in low peptides spectra. Further literature search revealed that both uricase and ornithine carbamoyltransferase are involved in the metabolic pathway producing urea. It was thus postulated that P. otitidis strain SN1 may possess two metabolic pathways (uricolysis and argininolysis) and thus, able to exhibit dual enzyme activity (uricase and ornithine carbamoyltransferase). This study is the first to report the characteristic of uricase producing bacterium, P. otitidis strain SN1 isolated from hot spring, and also suggesting the hot spring as potential source of new uricase.